The Dowers of the Angevin Queens: A Comparative Study - Storey, Gabrielle (De Medio Aevo, 2025)
This article is a comparative study of the dower lands of the Angevin queens of England (1154-1216) Eleanor of Aquitaine, Berengaria of Navarre, and Isabella of Angoulême. It outlines the background to the queenly demesne in the twelfth century and the lands granted to the three queens. It also discusses their access to these lands and how their power and exercise thereof was hindered by a lack of financial revenues, examining each queen as a case study. It then concludes with an overall summary of the importance of comparative studies in opening up new understandings of queenly power and authority in the twelfth and thirteenth centuries. Within the context of the conflict and political upheaval in the Angevin Union at the end of the twelfth century, it is evident that conquest as much as competition played a defining role in a queen’s access to lands.